2013
DOI: 10.1161/hypertensionaha.111.00627
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 Activation Improves Endothelial Function

Abstract: Diminished release and function of endothelium-derived nitric oxide (NO) coupled with increases in reactive oxygen species (ROS) production is critical in endothelial dysfunction. Recent evidences have shown that activation of the protective axis of the renin-angiotensin system composed by angiotensin-converting enzyme2 (ACE2), Angiotensin-(1-7) [Ang-(1-7)] and Mas receptor promotes many beneficial vascular effects. This has led us to postulate that activation of intrinsic ACE2 would improve endothelial functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 34 publications
3
72
0
2
Order By: Relevance
“…The present study shows that ACE2 overexpression both in vivo and ex vivo by ACE2 adenovirus transduction rescued the impaired EDRs in aortas and FMD in resistance mesenteric arteries from diabetic mice, which was consistent with earlier studies on ApoE -/ -mice and spontaneously hypertensive stroke-prone rats (29,43). Recently, ACE2 priming by the pharmacological activator, xanthenone (XNT), has been shown to protect the function of endothelial progenitor cells in hypertension and diabetes (5,11,18,23). In the present study, we have used a newly discovered ACE2 activator, DIZE (20,40,46), and shown that it enhances ACE2 activity in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…The present study shows that ACE2 overexpression both in vivo and ex vivo by ACE2 adenovirus transduction rescued the impaired EDRs in aortas and FMD in resistance mesenteric arteries from diabetic mice, which was consistent with earlier studies on ApoE -/ -mice and spontaneously hypertensive stroke-prone rats (29,43). Recently, ACE2 priming by the pharmacological activator, xanthenone (XNT), has been shown to protect the function of endothelial progenitor cells in hypertension and diabetes (5,11,18,23). In the present study, we have used a newly discovered ACE2 activator, DIZE (20,40,46), and shown that it enhances ACE2 activity in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…However, it should be noted that Ang-(1-7) did not relax the denuded aorta by itself when the effect of ACh was tested. This result is similar to that reported in vitro for the MasR agonist [50] and could stem from the importance of intact endothelium in ACh activity.…”
Section: Discussionsupporting
confidence: 91%
“…Neither AIA nor Ang-(1-7) changed SNP relaxation. The result of Ang-(1-7) is similar to that reported for MasR agonist [50] . These results suggest that AIA does not disturb smooth muscle activity, and Ang-(1-7) activities are not directly displayed via SNP-acted mechanisms in the smooth muscle of aorta.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Studies involving the activation of ACE2 further confirm the role of ANG-(1-7) axis cardiovascular dysfunction. Either pharmacological or genetic activation of ACE2 improved endothelial migration, and impaired tube formation in renin transgenic mice and endothelial dysfunction in SHR rats (57,58). ACE2 activation has been reported to enhance the reparative function of endothelial progenitor cells in the diabetic condition (59).…”
Section: Discussionmentioning
confidence: 99%